PERANCANGAN SISTEM PENGGAJIAN TERKOMPUTERISASI DENGAN MENGGUNAKAN SQL SERVER 2005 DAN DELPHI 2007 PADA PIZZA HUT DELIVERY (PHD) CABANG KETINTANG SURABAYA - SETIAWAN, CHAIRUL (Jurnal Akuntansi AKUNESA, 2014)
Payroll is one of the important elements on a company. The company must have a great system in the determination of salaries to employees of the company can be loyal to the company. PHD still use a manual payroll system for non-permanent employees, it would require an automated payroll system to the determination of optimal payroll. Automatic payroll system can be created by using SQL Server 2005 and Delphi 2007. After that the system that has been created is implemented according to the needs of the company. The result of this payroll system can facilitate in determining the non-permanent employees salary is calculation has been done manually. And also can resolve the weaknesses of the previous system.   Keywords: payroll, SQL Server 2005, Delphi 2007.